Accountability management for multi-tenant cloud services. (2019) - Masmoudi, Fatma; Sellami, Mohamed; Loulou, Monia; Kacem, Ahmed Hadj
The widespread adoption of multi-tenancy in the Software as a Service delivery model triggers several data protection issues that could decrease the tenants' trustworthiness. In this context, accountability can be used to strengthen the trust of tenants in the cloud through providing the reassurance of the processing of personal data hosted in the cloud according to their requirements. In this paper, we propose an approach for the accountability management of multi-tenant cloud services allowing: compliance checking of services behaviours with defined accountability requirements based on monitoring rules, accountability-violation detection otherwise, and post-violation analysis based on evidences. A tool-suite is developed and integrated into a middleware to implement our proposal. Finally, experiments we have carried out show the efficiency of our approach relying on some criteria.